A Photoinduced Cascade for the Synthesis of 1H‐Indole‐2‐Acetamide Derivatives. Issue 7 (20th May 2019) - Borger, Maribel; Callen, Daniel P.; Frederich, James H.
Abstract: Readily prepared 3‐(2‐aminoaryl)‐6‐aminopyridazine N ‐oxides undergo a photoinduced cascade transformation to furnish 1 H ‐indole‐2‐acetamides. The reported method uniquely proceeds via acid‐catalyzed isomerization of a 2‐aminofuran intermediate and supports modular synthetic entry to indole derivatives that would be difficult to access by any other means. Abstract : Transient photo : A method to convert 2‐aminoaryl‐substituted pyridazine N ‐oxides to 1 H ‐indole‐2‐acetamides under the synergic action of UV light and transition‐metal catalysis is reported. This photoinduced cascade reaction passes through a transient 2‐aminofuran intermediate and facilitates synthetic entry to indole motifs that are unavailable by conventional methods.